Causal relationship between gut microbiota and diabetic neuropathy: a Mendelian randomization and 16S rRNA sequencing analysis - Hu, Yingqing; Liang, Yanqiu; Lv, Youyou; Mu, Panwei; Wang, Ying; Huang, Dingbang; Liu, Dezhao (Frontiers in Endocrinology, 2025)
ObjectivesEvidence suggests a link between gut microbiota and diabetes mellitus, yet the specific role in diabetic peripheral neuropathy (DPN) remains elusive. The study aims to explore the association through Mendelian randomization and 16S rRNA gene sequencing analysis.Materials and methodsMendelian randomization (MR) analysis was employed to investigate the causal association between gut microbiota and diabetic neuropathy. Diabetes mellitus (DM) and DPN mice models were developed via high-fat diet (HFD) feeding followed by intraperitoneal streptozotocin (STZ) administration at 30 mg/kg (DM group) or 60 mg/kg (DPN group). The occurrence of diabetic neuropathy was determined by evaluating pain-related behavioral parameters in mice. Additionally, fecal samples from mice and patients with diabetic neuropathy were collected, and 16S rRNA sequencing was performed to analyze the composition of gut microbiota.ResultsMendelian randomization analysis identified 14 gut microbiota species exhibiting a causal relationship with diabetic neuropathy. In animal studies, diabetic neuropathy mice exhibited decreased mechanical pain thresholds and reduced thermal withdrawal latency. Sequencing analyses further revealed significant alterations in gut microbiota composition in both DPN mice and DPN patients compared to control group.ConclusionThis study integrates Mendelian randomization analysis with 16S rRNA fecal assessments from animal models and clinical patients, revealing that gut microbiota imbalances may contribute to diabetic neuropathy development and providing novel insights for its prevention and therapeutic strategies.